E-module Using FlipHTML5 Application on Chemical Bond Material - Nelly Nurhayati; Roza Linda; Lenny Anwar (Jurnal Pendidikan Kimia Indonesia, 2022)
The low use of creative teaching materials following technological developments impacts student motivation and learning outcomes. This study aims to develop e-modules using the FlipHTML5 application on chemical bonding material. The types and sources of data are qualitative (suggestions and comments from the validator team and respondents) and quantitative (scores ​​from the validator team and respondents). The research subjects were 24 students and three chemistry teachers. The analysis technique used is the validity analysis technique using a Likert scale of 1 to 5 and a user response questionnaire. The results of the validation data analysis on the feasibility aspects of content, language, presentation, graphics, and application utilization were 88%, 86%, 96.67%, 83.33%, and 82.85%, respectively, with very valid criteria. E-modules obtained valid criteria according to the validator and were tested for responses to three chemistry teachers and 24 students. The results of the average percentage of student and teacher responses were 98.43% and 88.52%, respectively. The conclusion obtained from the results of the data analysis is that the resulting e-module using the FlipHTML5 application on chemical bond material is valid and can be used in the learning process.